Larvicidal efficacy of plant extracts and isolated compounds from Annonaceae and Piperaceae against Aedes aegypti and Aedes albopictus - Alzeir M Rodrigues; Victor Emanuel P Martins; Selene M Morais (Asian Pacific Journal of Tropical Medicine, 2020)
The Aedes (Ae.) aegypti and Ae. albopictus mosquitoes are vectors of epidemiologically relevant arboviruses in the public health context, such as the dengue, Zika and chikungunya viruses. Among the alternatives to synthetic insecticides for the control of these vectors, the use of natural plant products deserves attention. This review summarizes findings on the larvicidal potential of plant extracts on Ae. aegypti and Ae. albopictus, as well as the potential of isolated compounds from plants of the Annonaceae and Piperaceae families against these vectors. Descriptors related to larvicidal activity of plant extracts and isolated compounds in Aedes spp. in the Web of Science database were used, for plant extracts considering publications between 2000 and 2019. A total of 859 articles were analyzed for plant extracts and estimates of lethal concentration values (LC50 and LC90). In the end, 95 articles that presented the larvicidal potential of 150 plant species from 52 families were analyzed. The two families most studied for this activity were Fabaceae and Asterace Aedes. The plant families with the best LC50 values against mosquitoes were Piperaceae and Annonaceae. Larvicidal activity of 50 acetogenins has already been identified on Ae. aegypti, and 29 of them presented LC50 below 10 μg/mL, as well as the larvicidal activity of 8 compounds isolated from Piperaceae. Therefore, plants of these two families are promising for the development of commercial botanical larvicides in the form of extracts and isolated substances, as well as the production via organic synthesis of the most active compounds.